Cadmium-Tolerant Rhizospheric Bacteria of the C3/CAM Intermediate Semi-Halophytic Common Ice Plant (Mesembryanthemum crystallinum L.) Grown in Contaminated Soils - Supel, Paulina; Śliwa-Cebula, Marta; Miszalski, Zbigniew; Kaszycki, Paweł (Frontiers in Plant Science, 2022)
The common ice plant, Mesembryanthemum crystallinum L., has recently been found as a good candidate for phytoremediation of heavy-metal polluted soils. This semi-halophyte is a C3/CAM (Crassulacean acid metabolism) intermediate plant capable of tolerating extreme levels of cadmium in the soil. The aim of the work was to preliminary characterize the soil microbiota of M. crystallinum grown in Cd-contaminated substrates as dependent on the type of photosynthetic metabolism. The plants performing either C3 or CAM photosynthesis were treated for 8 days with variant CdCl2 doses to obtain final Cd concentrations ranging from 0.82 to 818 mg·kg-1 of soil d.w. The CAM phase was induced by highly saline conditions. After treatment, eighteen bacterial and three yeast strains were isolated from the root zones and, after preliminary Cd-resistance in vitro test, five bacterial strains were selected and identified with a molecular proteomics technique. Two strains of the species Providencia rettgeri (W6 and W7) were obtained from the C3 phase and three (one Paenibacillus glucanolyticus S7 and two Rhodococcus erythropolis strains: S4 and S10) from the CAM performing plants. The isolates were further tested for Cd-resistance (treatment with either 1 mM or 10 mM CdCl2) and salinity tolerance (0.5 M NaCl) in model liquid cultures (incubation for 14 days). Providencia rettgeri W7 culture remained fully viable at 1 mM Cd, whereas Rh. erythropolis S4 and S10 together with Paenibacillus glucanolyticus S7 were found to be resistant to 10 mM Cd in the presence of 0.5M NaCl. It is suggested that the high tolerance of the common ice plant towards cadmium may result from the synergic action of the plant together with the Cd/salt-resistant strains occurring within rhizospheral microbiota. Moreover, the isolated bacteria appear as promising robust microorganisms for biotechnological applications in bio- and phytoremediation projects.